12th World Youth and Students Festival - IBIK MA; Karakashev, V; Levzhunova, L; Lukanov, M; Serebrakov, G; Feklaev, V (СПК ХII ВФМС, 1985)
Colourful poster with dove; stylized representation of African person in profile PO-0402